Innovative method of cross infection minimization using novel through-glass technique in portable chest radiography / Mohd Hafizi Mahmud ... [et al.] - Mahmud, Mohd Hafizi; Zakaria, Faikah; Sharip, Hairenanorashikin; Mohamad, Noor Shafini; Che Zakaria, Wan Farah Wahida; Baharuddin, Nur Aiman (2022)
Portable chest radiography is a standard radiological procedure routinely used for bedside patients. COVID-19 pandemic has presented several challenges, including cross infection between the healthcare personnel and patients and a shortage of personal protective equipment (PPE). Hence, healthcare personnel-patient contact should be minimised as best as possible. This project is aimed to evaluate the image acceptability of portable chest radiography using through-glass technique as an innovative method in radiological procedure. On the hospital bed, a 35 cm x 43 cm imaging plate was arranged against the anthropomorphic thorax phantom, and the portable x-ray machine was positioned at a 200 cm source-image-distance (SID). The phantom was exposed using the standard and through-glass techniques with two exposure parameters of anterior-posterior (AP) chest radiography (80 kVp, 5 mAs and 90 kVp, 5 mAs). The radiographs were blindly reviewed by two senior radiographers based on the standard diagnostic image acceptability criteria. An inter-rater reliability using Cohen’s kappa analysis was performed to determine the consistency among the evaluators. A statistically significant with moderate agreement between the two evaluators was observed for the chest radiographs from both sets of exposure parameters (kappa value, k = 0.6, p < 0.05). Portable chest radiography using through-glass technique showed equivalent image quality of the standard chest radiography technique and complied with the diagnostic image acceptability. This novel technique has a potential clinical application to minimise cross-infection risk during the radiological procedure.